2012
DOI: 10.1038/onc.2012.72
|View full text |Cite
|
Sign up to set email alerts
|

A potent Chk1 inhibitor is selectively cytotoxic in melanomas with high levels of replicative stress

Abstract: There are few effective treatments for metastatic melanoma. Checkpoint kinase 1 (Chk1) inhibitors are being trialled for their efficacy in enhancing conventional chemotherapeutic agents, but their effectiveness as single agents is not known. We have examined the effectiveness of two novel Chk1 selective inhibitors, AR323 and AR678, in a panel of melanoma cell lines and normal cell types. We demonstrate that these drugs display single-agent activity, with IC50s in the low nanomolar range. The drugs produce cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(111 citation statements)
references
References 40 publications
9
102
0
Order By: Relevance
“…33 In addition, our data provides a novel explanation for the observed pattern of H2AX phosphorylation associated to E1a expression trough RS mediated by c-Myc rather than through ATM-dependent mechanism. 37 Finally, regarding the role of Chk1 in E1a-expressing cells, our data support the idea that this could be a key element to maintain viability in these cells, as has been shown in c-Myc-driven tumorgenesis or in melanoma, 32,38 and even could be implicated in the transforming properties of E1a as has been shown in other experimental systems.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…33 In addition, our data provides a novel explanation for the observed pattern of H2AX phosphorylation associated to E1a expression trough RS mediated by c-Myc rather than through ATM-dependent mechanism. 37 Finally, regarding the role of Chk1 in E1a-expressing cells, our data support the idea that this could be a key element to maintain viability in these cells, as has been shown in c-Myc-driven tumorgenesis or in melanoma, 32,38 and even could be implicated in the transforming properties of E1a as has been shown in other experimental systems.…”
Section: Discussionsupporting
confidence: 73%
“…4D and E). Considering recent evidences showing how Chk1 inhibitors selectively kill cells with a marked RS, 32,38 we decided to challenge E1a-expressing cells to Chir-124, a known inhibitor for Chk1. 39 Interestingly, E1a cells showed a higher toxicity in response to Chir-124 (Fig.…”
Section: C-myc Meditates E1a Effects On Chk1mentioning
confidence: 99%
“…Although targeting such intra-S functions of ChK1 in the face of mounting replication stress can result in replication fork collapse and a significant induction of DSBs, we have found that chemo combinations with this mechanism of action are poorly tolerated in animals, even with extensive modification to both dose and schedule (e.g., thymidine monophosphate depletion with Xeloda; data not shown). However, the synthetic lethal potential of ChK1 inhibition may provide single-agent activity in cancers with a high degree of replicative stress (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, based on the concept that many tumors exhibit high levels of replicative stress, the sole inhibition of Chk1 has been shown to effectively target melanoma cells with significant intrinsic DNA damage (Brooks et al, 2013). The cytotoxic effect of Chk1 inhibitors resulted from inhibition of Chk1 activity in the S phase driving premature exit from the S phase into an aberrant mitosis, resulting in either failure of cytokinesis or cell death by an apoptotic mechanism.…”
Section: Mk2 Neuroinflammation and Cell Cyclementioning
confidence: 99%